2005
DOI: 10.1080/0013188042000337604
|View full text |Cite
|
Sign up to set email alerts
|

Sociometry as a method for investigating peer relationships: what does it actually measure?

Abstract: In sociometric research tradition, popularity is defined as the degree to which children are liked or accepted by their peers. However, research indicates that two definitions of popular students should be distinguished: (1) popular students as those students who are well liked by many and disliked by few peers, and (2) popular students as those students who are described as popular by their peers. The main purpose of the present study was to examine the relationship between sociometric and peer perceived popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 46 publications
1
14
0
4
Order By: Relevance
“…Following the logic of social preference scores, some compute a difference of most popular minus least popular standardized nominations as a measure of perceived popularity (Cillessen & Mayeux, 2004a ;Closson, 2009aClosson, , 2009bKo š ir & Pe č jak, 2005 ) or perceived preference (Kuppens, Grietens, Onghena, Michiels, & Subramanian, 2008 ;Lease et al, 2002 ). Most commonly, perceived popularity or preference is treated as a continuous variable, although some have used cutoff scores (typically ± 0.5 or 1 SD) to classify youth into status categories (e.g., Closson, 2009a ;Ko š ir & Pe č jak, 2005 ;Kuppens et al, 2008 ;LaFontana & Cillessen, 1999 ;.…”
Section: Measurement Of Perceived Popularitymentioning
confidence: 99%
See 1 more Smart Citation
“…Following the logic of social preference scores, some compute a difference of most popular minus least popular standardized nominations as a measure of perceived popularity (Cillessen & Mayeux, 2004a ;Closson, 2009aClosson, , 2009bKo š ir & Pe č jak, 2005 ) or perceived preference (Kuppens, Grietens, Onghena, Michiels, & Subramanian, 2008 ;Lease et al, 2002 ). Most commonly, perceived popularity or preference is treated as a continuous variable, although some have used cutoff scores (typically ± 0.5 or 1 SD) to classify youth into status categories (e.g., Closson, 2009a ;Ko š ir & Pe č jak, 2005 ;Kuppens et al, 2008 ;LaFontana & Cillessen, 1999 ;.…”
Section: Measurement Of Perceived Popularitymentioning
confidence: 99%
“…Sociometric and perceived popularity demonstrate differential links to social behavior (e.g., Babad, 2001 ;Parkhurst & Hopmeyer, 1998 ;Sandstrom & Cillessen, 2006 ), particularly during adolescence (Cillessen & Borch, 2006 ;Cillessen & Mayeux, 2004a ;Ko š ir & Pe č jak, 2005 ;LaFontana & Cillessen, 2002 ;Schwartz et al, 2006 ;Vaillancourt & Hymel, 2006 ). For example, among middle childhood and adolescent students in Italy, colleagues (2009, 2010) found that bullying was associated negatively with sociometric popularity (social preference) but positively with perceived popularity.…”
Section: Perceived Popularity Versus Sociometric Popularity: Distinctmentioning
confidence: 99%
“…Reprenant cette problématique dans une publication plus récente encore, Košir et Pečjak (2005) observent une différence plus marquée entre le statut sociométrique et la popularité perçue par les pairs chez les adolescents. En effet, si les deux évaluations sont moyennement corrélées à l'âge de 11 ans, elles apparaissent comme indépendantes chez les élèves de 17 ans.…”
Section: Sociométrie Et Popularité : Deux Concepts Différentsunclassified
“…Koristeći se nominacijama sviđanja i nesviđanja, istraživači mogu odrediti položaj sudionika na dvjema dimenzijama. Oduzimanjem broja nominacija sviđanja i nesviđanja razlikujemo djecu i adolescente na dimenziji socijalne preferencije, a njihovim zbrajanjem na dimenziji socijalnog utjecaja (Košir i Pečjak, 2005.). Kombiniranjem standardiziranih rezultata na navedenim dvjema dimenzijama dobivamo pet sociometrijskih kategorija.…”
Section: Uvodunclassified